Trauma in the creative and embodied therapies : when words are not enough - Chesner, Anna; Lykou, Sissy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Trauma in the creative and embodied therapies is a cross-professional book looking at current approaches to working therapeutically and socially with trauma in a creative and embodied way. The book pays attention to different kinds of trauma; environmental, sociopolitical, early relational, abuse in its many forms and the trauma of illness, with contributions from international experts, drawn from the fields of the arts therapies, the embodied psychotherapies, as well as nature-based therapy and playback theatre. The book is divided into three sections: the first section takes into consideration the wider sociopolitical perspective of trauma and the power of community engagement. In the second section there are numerous clinical approaches to working with trauma, whether with individuals or groups, highlighting the importance of creative and embodied approaches. In the third section the focus shifts from client work to the impact of trauma on the practitioner, team and supervisor, and the importance of creative self-care and reflection in managing this challenging field. This book will be useful for all those working in the field of trauma, whether as clinicians, artists or social workers"--
Part 1 -- Wider Perspective -- Chapter 1: Sociopolitical perspectives on trauma in a world in crisis: 'the personal is political' revisited by Sissy lykou -- Chapter 2: Enacting testimony: trauma stories in playback theatre by Jo Salas -- Part 2 -- Clinical Perspectives -- Chapter 3: The unplayable piano: from discord to harmony: trauma, play therapy and the power of the non-verbal by David Le-Vay -- Chapter 4: As time goes by... Music psychotherapy and trauma by Julie Sutton -- Chapter 5: Healing trauma through embodied relating: Re-establishing rhythms of relating by Gill Westland -- Chapter 6: Psychodrama and healing the traumatic wound by Anna Chesner -- Chapter 7: Building resilience: Developing embodied and relational resources in a Gestalt movement therapy group -- for women with borderline personality disorder and histories of profound trauma by Yeva Feldman -- Chapter 8: Dance movement psychotherapy: the body tells the unspeakable by Marianne Eberhard-Kaechele -- Chapter 9: The warrior's journey by Linda Winn -- Chapter 10: Letting go of the spider by Aileen Webber and Sophia Condaris -- Chapter 11: An elemental relationship: Nature-based trauma therapy by Hayley Marshall -- Part 3 -- The impact of trauma on the therapist and embodied supervisory approaches -- Chapter 12: Secondary traumatisation and therapist illness by Ditty Dokter, Lisa Lea-Weston and Tara Thornewood -- Chapter 13: Movement observation in trauma-centred case supervision by Claire Schaub-Moore
OCLC-licensed vendor bibliographic record.
Keywords: Psychic trauma -- Treatment; Art therapy; Arts -- Therapeutic use; Drama -- Therapeutic use; Mind and body therapies; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health